-4(-3.6-1.7x)=46.4-1.2x

Simple and best practice solution for -4(-3.6-1.7x)=46.4-1.2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-3.6-1.7x)=46.4-1.2x equation:


Simplifying
-4(-3.6 + -1.7x) = 46.4 + -1.2x
(-3.6 * -4 + -1.7x * -4) = 46.4 + -1.2x
(14.4 + 6.8x) = 46.4 + -1.2x

Solving
14.4 + 6.8x = 46.4 + -1.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.2x' to each side of the equation.
14.4 + 6.8x + 1.2x = 46.4 + -1.2x + 1.2x

Combine like terms: 6.8x + 1.2x = 8x
14.4 + 8x = 46.4 + -1.2x + 1.2x

Combine like terms: -1.2x + 1.2x = 0.0
14.4 + 8x = 46.4 + 0.0
14.4 + 8x = 46.4

Add '-14.4' to each side of the equation.
14.4 + -14.4 + 8x = 46.4 + -14.4

Combine like terms: 14.4 + -14.4 = 0.0
0.0 + 8x = 46.4 + -14.4
8x = 46.4 + -14.4

Combine like terms: 46.4 + -14.4 = 32
8x = 32

Divide each side by '8'.
x = 4

Simplifying
x = 4

See similar equations:

| (x/7)=14 | | 21=v+2 | | 11/2z-(-1/2-5/2z)=-9/2 | | r^2+2r-288=0 | | 8z+6-4z=30-4z | | 39x+3+8x=144 | | (26w^2)(52w)=9360 | | 8x-2(5-x)=11 | | (26w^2)x(52w)=9360 | | -(-4/3+3p)=19/3-5p | | 9x+4-2x=7x-6+x | | 26w^2+52w=9360 | | (y/3)+(y/4)=(5/6) | | (a/3)=333 | | -(4/3+3p)=19/3-5p | | -4=b-2 | | 3a+4=2a+5 | | (a*3)=333 | | 3x+11+2x+4x=75 | | r^2+2r-143=0 | | -5x+16=-44 | | (X+2)=5(x+4) | | 1.9+6.6n=-2.5n-3(-3n-0.6) | | -3.2x=-28.8 | | 2c-3=6c+25 | | -4(-1.6-8.2n)=11.4+33.8n | | -13+5=x+8 | | -4(1.6-8.2n)=11.4+33.8n | | 3+8+x=4+7 | | 4x+10+18x-10=120 | | 7n-(1+3n)=-8 | | -5x+4(-3+4x)=-10.8+10.6x |

Equations solver categories